РОССИЯ ИМПЕРИЯСЫНЫҢ ЖАЎЛАП АЛЫЎЫНЫҢ ҚАРАҚАЛПАҚ ХАЛҚЫ МӘДЕНИЯТЫНА ТӘСИРИ - Бекбаўлиева, Н.Б. (ILIM hám JÁMIYET, 2024)
This article discusses the conquest of the Karakalpaks by Tsarist Russia and its impact on the culture of the people. It also attempts to shed light on the persistence of traditional customs and rituals in the face of significant political and cultural changes in the lives and daily routines of the people.